High-phase-purity ferric sodium pyrophosphate / carbon material as well as preparation method and application thereof
In the synthesis process of sodium ion battery positive electrode materials, the solution mixing and spray drying technology of soluble raw materials is used, combined with sand grinding and specific atmosphere roasting technology, the problems of poor mixing uniformity of raw materials and carbon coating effect are solved, and the preparation of sodium ferrophosphate phosphate/carbon material with high phase purity and excellent conductivity is achieved.
Patent Information
- Application Number
- CN202510003623.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, when synthesizing sodium ion battery positive electrode material sodium phosphate/carbon, the raw material mixing uniformity and poor carbon coating effect, resulting in low material phase purity and poor conductivity.
The solution mixing is performed using soluble raw materials, and the ionic mixing and carbon coating of the raw materials are achieved through spray drying and sand grinding. Combined with the roasting process of specific atmosphere and temperature conditions, the decomposition reaction rate is controlled to ensure uniform mixing of raw materials and uniform carbon coating.
A sodium ferro pyrophosphate/carbon material with high phase purity and excellent conductivity is obtained, which significantly improves the capacity and rate performance of sodium ion batteries.
Smart Images

Figure BDA0005226208830000121 
Figure BDA0005226208830000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion battery positive electrode materials, and specifically relates to a high-purity sodium iron phosphate pyrophosphate / carbon material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have been widely studied. The low cost, high abundance and wide distribution of sodium resources make sodium electricity a very promising route for electrochemical energy storage.
[0003] At present, sodium-ion batteries have been widely studied and reported, such as vanadium-based phosphates, iron-based phosphates, Prussian blue analogs and metal layered oxides. With the deepening of research, the performance of sodium-ion batteries has been continuously improved, but many problems have also been gradually exposed, such as the high cost and toxicity of vanadium-based materials, the unstable structure of Prussian blue materials, and the high price of layered oxides. The sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7) material in iron-based phosphate combines the advantages of all iron-based phosphates: environmental friendliness, low cost, high theoretical capacity (129mAh g -1 ), with a high average working voltage (3.1V) and low volume expansion (<4%), it is considered to be the most promising positive electrode material for sodium ion batteries. The theoretical stoichiometric ratio of sodium, iron and phosphorus sources in conventional synthesis is 4:3:4, but the traditional solid phase method uses sand milling to mix the raw materials, which usually has the problem of uneven mixing of raw materials. The synthesized stoichiometric ratio Na4Fe3(PO4)2P2O7 is always accompanied by the generation of NaFePO4 and NaFeP2O7 impurities, which seriously affects the capacity and rate performance of the material.
[0004] In the prior art, the uniformity of raw material mixing and the carbon coating effect deteriorate during the roasting process, resulting in low phase purity and poor conductivity of the generated Na4Fe3(PO4)2P2O7 / C material.
[0005] Therefore, the development of a sodium iron pyrophosphate / carbon material that can synthesize high phase purity and good coating effect is of great significance for the development of sodium ion batteries. Summary of the invention
[0006] One of the purposes of the present invention is to provide a method for preparing sodium iron phosphate pyrophosphate / carbon material. The method selects soluble raw materials and cooperates with a unique roasting process to achieve high raw material mixing uniformity and good carbon coating uniformity, and the obtained Na4Fe3(PO4)2P2O7 / C material has high phase purity and good electrical conductivity, thereby having excellent electrical properties.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:
[0008] A method for preparing a sodium iron pyrophosphate / carbon material, the method comprising the following steps:
[0009] S1: preparing a soluble sodium source, an iron source, and a phosphorus source into a solution, and drying the solution to obtain a mixed raw material;
[0010] S2: high temperature treatment of the mixed raw materials to obtain precursor-1;
[0011] S3: disperse precursor-1, add carbon source, sand grind, and dry to obtain precursor-2;
[0012] S4: treating the precursor-2 at high temperature to obtain sodium iron pyrophosphate / carbon material.
[0013] Among the patents on sodium iron pyrophosphate materials that have been publicly reported, many patents include soluble raw materials such as ferric nitrate, ferrous sulfate, etc. when defining the types of raw materials (such as patents CN112768673B, CN118588930A, CN118666260A, CN117682490A), but the preparation method does not distinguish between them and insoluble raw materials (such as ferric phosphate, ferrous oxalate, etc.). It should be pointed out that soluble raw materials will decompose in a short time during the roasting process to produce a large amount of gas (such as NOx, SOx). These gases will cause the raw material mixing uniformity to deteriorate and the carbon coating effect to deteriorate during the roasting process, resulting in the generated Na4Fe3(PO4)2P2O7 / C material with low phase purity and poor conductivity. The present invention has been found that by selecting soluble raw materials, ionic mixing of the raw materials in the solution is achieved, thereby maximizing the mixing uniformity of the raw materials. In order to solve the problem of generating a large amount of gas due to decomposition in a short period of time during the roasting process, roasting is performed under a specific atmosphere to increase the concentration of decomposition products in the roasting atmosphere, thereby effectively controlling the rate of the decomposition reaction and slowing down the decomposition process. During the roasting process, the raw materials are still in a uniformly mixed state, and the coating uniformity of the carbon source is effectively guaranteed.
[0014] In one embodiment of the present invention, the sodium source in S1 is one or more of sodium dihydrogen phosphate, sodium phosphate, and sodium carbonate, preferably sodium dihydrogen phosphate and / or sodium carbonate.
[0015] In one embodiment of the present invention, the iron source in S1 is one or more of ferric nitrate, ferrous sulfate, ferric chloride, ferrous chloride, and ferric sulfate, preferably ferric nitrate and / or ferrous sulfate.
[0016] In one embodiment of the present invention, the phosphorus source in S1 is one or more of sodium dihydrogen phosphate, sodium monohydrogen phosphate, phosphoric acid, and ammonium dihydrogen phosphate, preferably sodium dihydrogen phosphate and / or phosphoric acid; preferably, the molar ratio of sodium, iron, and phosphorus elements is 4:(2.6-3.4):(3.6-4.4).
[0017] In one embodiment of the present invention, the mass concentration of the soluble raw materials in the solution in S1 is 10-40%.
[0018] In one embodiment of the present invention, the drying method in S1 is spray drying, preferably spray drying in the form of two-fluid atomization.
[0019] In one embodiment of the present invention, the high temperature treatment in S2 is carried out in a fluidized bed or a rotary kiln. The treatment equipment is commonly used in the art.
[0020] In one embodiment of the present invention, the atmosphere for high temperature treatment in S2 is a nitrogen oxide and / or sulfur oxide atmosphere, and optionally an inert gas, preferably the nitrogen oxide and / or sulfur oxide atmosphere is NO2 and / or SO3.
[0021] In one embodiment of the present invention, the pressure of the high temperature treatment in S2 is a gauge pressure of 10 kPa to 200 kPa.
[0022] In one embodiment of the present invention, the intake air volume of the high temperature treatment in S2 is 0.2-10 L / min.
[0023] In one embodiment of the present invention, the high temperature treatment in S2 is performed at a temperature of 200-450° C. and for a time of 2-20 h.
[0024] In one embodiment of the present invention, the carbon source in S3 is one or more of glucose, citric acid, polyethylene glycol, sucrose, starch, and cyclodextrin, preferably one or more of glucose, citric acid, and polyethylene glycol.
[0025] In one embodiment of the present invention, the molar ratio of the carbon source compound to the iron source compound in S3 is (0.05-0.25):1.
[0026] In one embodiment of the present invention, the drying method in S3 is spray drying, preferably spray drying in the form of two-fluid atomization.
[0027] In one embodiment of the present invention, S4 is treated at high temperature in an inert atmosphere and / or a reducing atmosphere; preferably, the inert atmosphere is one or more of nitrogen, argon, and helium, and the reducing atmosphere is hydrogen; preferably, the molar ratio of the inert atmosphere to the reducing atmosphere is 50 / 50 to 99 / 1.
[0028] In one embodiment of the present invention, S4 is treated at high temperature in a rotary kiln or a tubular furnace. The treatment equipment is commonly used in the art.
[0029] In one embodiment of the present invention, the pressure of the high temperature treatment in S4 is normal pressure.
[0030] In one embodiment of the present invention, the flow rate of the atmosphere during the high temperature treatment in S4 is 0.2-1 L / min.
[0031] In one embodiment of the present invention, the high temperature treatment in S4 is performed at a temperature of 400-600° C. and for a time of 2-20 h.
[0032] Another object of the present invention is to provide a high phase purity sodium iron phosphate pyrophosphate / carbon material.
[0033] A high-phase-purity sodium iron phosphate pyrophosphate / carbon material, the material is prepared by the above-mentioned preparation method, the mass ratio of sodium iron phosphate pyrophosphate to carbon in the material is 95:5-99:1; wherein the sodium iron phosphate pyrophosphate has a molecular formula of Na4Fe3(PO4)2P2O7, and the crystal phase purity is ≥99.5%.
[0034] Another object of the present invention is to provide a use of a high phase purity sodium iron pyrophosphate / carbon material.
[0035] A use of a high-phase-purity sodium iron phosphate pyrophosphate / carbon material, wherein the material is prepared by the above-mentioned preparation method or is the above-mentioned material, and the material is used as a positive electrode material for a sodium ion battery.
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] The present invention selects soluble sodium source, iron source, phosphorus source and carbon source as raw materials, and ensures the mixing uniformity of each element in the precursor to the greatest extent by means of solution mixing and rapid drying. By selecting a rotary kiln or a fluidized bed for the first stage of roasting, and setting reasonable roasting conditions, the raw material decomposition and gas production process is made uniform and controllable, avoiding the uneven distribution of raw materials caused by large and concentrated gas production; by sand milling and secondary carbon coating, the coating uniformity is improved. Through the method of the present invention, sodium iron pyrophosphate / carbon material with high phase purity and uniform carbon coating can be synthesized, which has excellent capacity and rate performance. DETAILED DESCRIPTION
[0038] The manufacturers and models of the experimental raw materials used are shown in the following table.
[0039] raw material factory Specifications Ferric Nitrate Sinopharm Reagents 98% Ferrous Sulfate Sinopharm Reagents 98% Ferric chloride aladdin 99% Ferrous chloride Sinopharm Reagents 98% Ferrous Sulfate Sinopharm Reagents 97% Sodium dihydrogen phosphate Sinopharm Reagents 99% Sodium phosphate Sinopharm Reagents 98% Sodium carbonate aladdin 98% Sodium monohydrogen phosphate aladdin 99% Phosphoric acid aladdin 85% Ammonium dihydrogen phosphate aladdin 99% glucose aladdin 98% Citric acid aladdin 99.5% Polyethylene glycol aladdin Molecular weight 200 sucrose Shanghai Test Reagent pure starch Sinopharm Reagents Analytical grade Cyclodextrin Wokai reagent 98%
[0040] The manufacturers and models of equipment used in the material preparation process are shown in the following table.
[0041] Device Name factory Specifications Spray Dryer Okawara OADB-8 Rotary kiln Hefei Kejing Materials Technology Co., Ltd. OTF-1200X-5L-R-III Fluidized Bed Kaimeisheng Petrochemical Equipment Co., Ltd. KFFB-10 Tube Furnace Tianjin Central SK-G06123K Sand grinder Dongguan Langling Intelligent Co., Ltd. NT-V2S
[0042] The manufacturers and models of instruments used for material analysis and performance testing are shown in the following table.
[0043] Device Name factory Specifications Battery Powder Compaction Density Tester Shenzhen Sansi UTM7305 Power-off test platform Newway CT-4000
[0044] Example 1
[0045] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0046] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0047] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0048] Example 2
[0049] Weigh 228g of ferrous sulfate and 312g of sodium dihydrogen phosphate and dissolve them in 8L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 200°C at 5°C / min and keep warm for 20h. The rotary kiln atmosphere is a mixed atmosphere of 10% SO3 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, a powder precursor-1 is obtained.
[0050] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0051] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0052] Example 3
[0053] Weigh 243g of ferric chloride and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 450°C at 5°C / min and keep warm for 2h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0054] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0055] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0056] Example 4
[0057] Weigh 606g of ferric nitrate, 212g of sodium carbonate, and 196g of phosphoric acid and dissolve them in 2.7L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, a powder precursor-1 is obtained.
[0058] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0059] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0060] Example 5
[0061] Weigh 606g of ferric nitrate, 212g of sodium carbonate, and 230g of ammonium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, a powder precursor-1 is obtained.
[0062] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0063] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0064] Example 6
[0065] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0066] Precursor-1 was added to 2L of deionized water, 28.8g of citric acid was added, and sand milled at a speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210°C, and outlet temperature 105°C. Precursor-2 was obtained.
[0067] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0068] Example 7
[0069] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0070] Precursor-1 was added to 2L of deionized water, 30g of polyethylene glycol (molecular weight 200g / mol) was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0071] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0072] Example 8
[0073] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0074] Precursor-1 was added to 2L of deionized water, 51.3g of sucrose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210°C, and outlet temperature 105°C. Precursor-2 was obtained.
[0075] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0076] Example 9
[0077] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 0.2L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0078] Precursor-1 was added to 2L of deionized water, 67.5g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0079] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0080] Example 10
[0081] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 10L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0082] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0083] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0084] Embodiment 11
[0085] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 200kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0086] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0087] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0088] Example 12
[0089] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 100kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0090] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0091] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0092] Example 13
[0093] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0094] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0095] Precursor-2 was placed in a tube furnace and calcined at 400° C. for 20 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0096] Embodiment 14
[0097] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, powder precursor-1 is obtained.
[0098] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0099] Precursor-2 was placed in a tube furnace and calcined at 600° C. for 2 h in a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0100] Embodiment 15
[0101] Weigh 525.2g of ferric nitrate, 212g of sodium carbonate, and 176.4g of phosphoric acid and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, a powder precursor-1 is obtained.
[0102] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0103] Precursor-2 was placed in a tube furnace and calcined in a nitrogen / hydrogen mixed atmosphere, wherein the nitrogen / hydrogen ratio was 99 / 1, and calcined at 500° C. for 12 h to obtain sodium iron phosphate pyrophosphate / carbon material.
[0104] Example 16
[0105] Weigh 686.8g of ferric nitrate, 212g of sodium carbonate, and 215.6g of phosphoric acid and dissolve them in 5L of deionized water. Spray dry to obtain a powder. Heat and keep the spray-dried material in a rotary kiln according to the following procedure: heat to 350°C at 5°C / min and keep warm for 10h. The rotary kiln atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, the rotary kiln pressure is 10kPa, and the rotation speed is 5 rpm. After treatment, a powder precursor-1 is obtained.
[0106] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0107] Precursor-2 was placed in a tube furnace and calcined in a nitrogen / hydrogen mixed atmosphere, wherein the nitrogen / hydrogen ratio was 50 / 50, and calcined at 500° C. for 12 h to obtain sodium iron phosphate pyrophosphate / carbon material.
[0108] Embodiment 17
[0109] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain powder. Heat and keep the spray-dried material in a fluidized bed according to the following procedure: heat to 350℃ at 5℃ / min and keep warm for 10h. The fluidized bed atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, and the fluidized bed pressure is 10kPa. After treatment, powder precursor-1 is obtained.
[0110] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0111] Precursor-2 was placed in a tube furnace and calcined at 500° C. for 12 h under a nitrogen atmosphere to obtain sodium iron pyrophosphate / carbon material.
[0112] Embodiment 18
[0113] Weigh 606g of ferric nitrate and 312g of sodium dihydrogen phosphate and dissolve them in 5L of deionized water. Spray dry to obtain powder. Heat and keep the spray-dried material in a fluidized bed according to the following procedure: heat to 350℃ at 5℃ / min and keep warm for 10h. The fluidized bed atmosphere is a mixed atmosphere of 10% NO2 and 90% N2, the gas velocity is 5L / min, and the fluidized bed pressure is 10kPa. After treatment, powder precursor-1 is obtained.
[0114] Precursor-1 was added to 2L of deionized water, 27g of glucose was added, and sand milling was performed at a sand milling speed of 2000rpm for 5h. After sand milling, a slurry was obtained, which was dried by spray drying. Two-fluid type spray drying was selected, and the process parameters were feed rate 1L / min, inlet temperature 210℃, and outlet temperature 105℃. Precursor-2 was obtained.
[0115] Precursor-2 was placed in a rotary kiln and calcined in a hydrogen / nitrogen atmosphere, wherein the ratio of hydrogen / nitrogen was 50 / 50, calcined at 500°C for 12 hours, the rotary kiln speed was 5 rpm, and the pressure was normal pressure to obtain sodium iron pyrophosphate / carbon material.
[0116] Comparative Example 1
[0117] Compared with Example 1, the only difference is that the rotary kiln atmosphere is N2 atmosphere, and the rest is the same as Example 1.
[0118] Application Examples
[0119] A 2032-type battery case was used, the positive electrode was a NFPP / C electrode prepared in the embodiment or the comparative example, the current collector was an aluminum foil, the active material (materials prepared in the embodiment and the comparative example): conductive carbon (acetylene black): PVDF = 80:10:10, the negative electrode was sodium metal, a fiber separator (model Whatman Grade GF / D) was used, and the electrolyte was 1M NaPF6 (EC:PC = 1:1, 5%
[0120] The battery was loaded with sodium ferric pyrophosphate (FEC); the standing time was 8 hours, a rate charge and discharge program was set, the rate was 50C (1C = 129mA / g), the voltage range was 1.7V-4.3V, and 2C cycled 1000 times; the theoretical specific capacity of sodium ferric pyrophosphate was 129mAh / g; the test results are shown in Table 1.
[0121] The comparison of crystal phase purity and electrical properties of the embodiment and the comparative example is shown in Table 1. The crystal phase purity and electrical properties of the sample synthesized in the embodiment are much higher than those of the comparative example, because by adopting the method provided in the present invention, the raw material decomposition process is effectively controlled, the gas production rate is slowed down, and the uniformity of raw material mixing and carbon coating is ensured, so that the synthesized material exhibits high phase purity, thereby obtaining excellent electrochemical performance.
[0122] Table 1 Material properties of different embodiments and comparative examples
[0123]
[0124]
[0125] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A method for preparing sodium iron pyrophosphate / carbon material, characterized in that: The preparation method comprises the following steps: S1: preparing a soluble sodium source, an iron source, and a phosphorus source into a solution, and drying the solution to obtain a mixed raw material; S2: high temperature treatment of the mixed raw materials to obtain precursor-1; S3: disperse precursor-1, add carbon source, sand grind, and dry to obtain precursor-2; S4: treating the precursor-2 at high temperature to obtain sodium iron pyrophosphate / carbon material.
2. The preparation method according to claim 1, characterized in that: The sodium source in S1 is one or more of sodium dihydrogen phosphate, sodium phosphate, and sodium carbonate, preferably sodium dihydrogen phosphate and / or sodium carbonate; And / or, the iron source in S1 is one or more of ferric nitrate, ferrous sulfate, ferric chloride, ferrous chloride, ferric sulfate, preferably ferric nitrate and / or ferrous sulfate; and / or, the phosphorus source in S1 is one or more of sodium dihydrogen phosphate, sodium monohydrogen phosphate, phosphoric acid, and ammonium dihydrogen phosphate, preferably sodium dihydrogen phosphate and / or phosphoric acid; Preferably, the molar ratio of sodium, iron and phosphorus is 4:(2.6-3.4):(3.6-4.4); and / or, the mass concentration of the soluble raw material in the solution in S1 is 10-40%; And / or, the drying method in S1 is spray drying, preferably spray drying in the form of two-fluid atomization.
3. The preparation method according to claim 1, characterized in that: In S2, high temperature treatment is carried out in a fluidized bed or a rotary kiln; and / or, the atmosphere for the high temperature treatment in S2 is a nitrogen oxide and / or sulfur oxide atmosphere, and optionally an inert gas, preferably the nitrogen oxide and / or sulfur oxide atmosphere is NO2 and / or SO3; and / or, the pressure of the high temperature treatment in S2 is 10 kPa to 200 kPa gauge pressure; and / or, the air intake volume for high temperature treatment in S2 is 0.2-10 L / min; And / or, the high temperature treatment in S2 is performed at a temperature of 200-450° C. and a time of 2-20 h.
4. The preparation method according to claim 1, characterized in that: The carbon source in S3 is one or more of glucose, citric acid, polyethylene glycol, sucrose, starch, and cyclodextrin, preferably one or more of glucose, citric acid, and polyethylene glycol; and / or, the molar ratio of the carbon source compound to the iron source compound in S3 is (0.05-0.25):1; And / or, the drying method in S3 is spray drying, preferably spray drying in the form of two-fluid atomization.
5. The preparation method according to claim 1, characterized in that: S4 is treated at high temperature in an inert atmosphere and / or a reducing atmosphere; Preferably, the inert atmosphere is one or more of nitrogen, argon, and helium, and the reducing atmosphere is hydrogen; Preferably, the molar ratio of the inert atmosphere to the reducing atmosphere is 50 / 50 to 99 / 1; and / or, S4 is treated at high temperature in a rotary kiln or a tube furnace; and / or, the pressure of the high temperature treatment in S4 is normal pressure; and / or, the flow rate of the atmosphere during the high temperature treatment in S4 is 0.2-1 L / min; And / or, the high temperature treatment in S4 is performed at a temperature of 400-600° C. and a time of 2-20 h.
6. A high phase purity sodium iron phosphate pyrophosphate / carbon material, which is prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of sodium ferric pyrophosphate to carbon in the material is 95:5-99:1; The molecular formula of the sodium iron pyrophosphate is Na4Fe3(PO4)2P2O7, and the crystal phase purity is ≥99.5%.
7. Use of a high-phase-purity sodium iron phosphate pyrophosphate / carbon material, wherein the material is prepared by the preparation method described in any one of claims 1 to 5, or is the material described in claim 6, and the material is used as a positive electrode material for a sodium ion battery.